A Study of Good Governance Administration at Pathumthani “Nanthamunee Bamrung” School under the Secondary Educational Service Area Office 4 - โกวิวัฒน์, ปาวีณา; อยู่เย็น, ศันสนีย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this study were: 1) to examine the level of administration based on the principles of good governance among teachers, and 2) to propose guidelines for developing administration based on the principles of good governance; also 3) to compare administration based on the principles of good governance, categorized by gender, age, education level, and work experience at Pathumthani “Nanthamunee Bamrung” School under the Secondary Educational Service Area Office 4, Pathum Thani Province. The population used in this study consisted of school administrators and teachers of Pathumthani “Nanthamunee Bamrung” School under the Secondary Educational Service Area Office 4, totaling 60 participants. The research instrument used for data collection was a closed-ended questionnaire. The statistics used for data analysis were percentages, mean, standard deviation, and t-test and F-test (one-way ANOVA).           The results of the study revealed that 1) the overall level of administration based on the principles of good governance among teachers at Pathumthani “Nanthamunee Bamrung” School was at a high level (µ = 4.12). When considering each aspect, most aspects were found to be at a high level. The aspects were ranked from the highest to the lowest mean as follows: value for money, accountability, transparency, morality, and participation. The rule of law was at a moderate level. 2) The guidelines for developing administration based on the principles of good governance suggested that school administrators should strictly adhere to good governance principles in administration by emphasizing fairness, transparency, and the public interest. In addition, administrators should encourage teachers and staff to participate in decision-making processes in school operations and give importance to building morale and motivation among teachers to enhance pride and motivation in their work, which would contribute to effective school administration based on the principles of good governance. 3) The results of administration based on the principles of good governance, classified by gender, age, education level, and work experience, revealed that teachers and educational personnel of different genders, age, education level, and work experience, had overall opinions on the aforementioned administration that did not differ.